2001
DOI: 10.1046/j.0953-816x.2001.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the myristoylated alanine‐rich C kinase substrate decreases uptake and K+‐evoked release of noradrenaline in the human neuroblastoma SH‐SY5Y

Abstract: The aim of this study was to investigate a possible role of the myristoylated alanine-rich C kinase substrate (MARCKS) in the mechanism of noradrenaline uptake and release in the human neuroblastoma cell line SH-SY5Y. A stable cell line showing a twofold overexpression of MARCKS was prepared by transfecting SH-SY5Y with pCEP4 containing MARCKS cDNA in the sense orientation. This cell line showed no changes in the expression of neurofilaments or markers of noradrenergic large dense-cored vesicles compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…MARCKS binds and crosslinks F-actin in a PKC phosphorylation-dependent manner (Hartwig et al, 1992;Bubb et al, 1999;Yarmola et al, 2001), and PKC-mediated phosphorylation of MARCKS results in the movement of synaptic vesicles from reserve pools to active release sites in cultured cells and synaptosomes (Vitale et al, 1995;Stevens and Sullivan, 1998;Walaas and Sefland, 2000;Rose et al, 2001;Yang et al, 2002). Furthermore, anti-MARCKS antibodies, or F-actin destabilizing agents, increase spontaneous neurotransmitter release in PC12 cells (Shoji-Kasai et al, 2002), whereas MARCKS overexpression (two-fold) impaired PKCinduced enhancement of neurotransmitter release in human neuroblastoma SH-SY5Y cells (Hartness et al, 2001). Therefore, a 50% reduction in MARCKS in mossy fiber axon terminals may compromise the regulation of F-actin cytoskeletal rigidity, resulting in less restriction in the movement of synaptic vesicles from reserve pools to active release sites.…”
Section: Discussionmentioning
confidence: 99%
“…MARCKS binds and crosslinks F-actin in a PKC phosphorylation-dependent manner (Hartwig et al, 1992;Bubb et al, 1999;Yarmola et al, 2001), and PKC-mediated phosphorylation of MARCKS results in the movement of synaptic vesicles from reserve pools to active release sites in cultured cells and synaptosomes (Vitale et al, 1995;Stevens and Sullivan, 1998;Walaas and Sefland, 2000;Rose et al, 2001;Yang et al, 2002). Furthermore, anti-MARCKS antibodies, or F-actin destabilizing agents, increase spontaneous neurotransmitter release in PC12 cells (Shoji-Kasai et al, 2002), whereas MARCKS overexpression (two-fold) impaired PKCinduced enhancement of neurotransmitter release in human neuroblastoma SH-SY5Y cells (Hartness et al, 2001). Therefore, a 50% reduction in MARCKS in mossy fiber axon terminals may compromise the regulation of F-actin cytoskeletal rigidity, resulting in less restriction in the movement of synaptic vesicles from reserve pools to active release sites.…”
Section: Discussionmentioning
confidence: 99%
“…Noradrenaline (NA) release from SH-SY5Y differentiated cells was measured according to Hartness et al (2001 …”
Section: Measurement Of [ 3 H]na Releasementioning
confidence: 99%
“…After differentiation, these cells are able to release NA after secretagogue treatment or depolarization, suggesting the acquisition of the neurosecretory competence (Encinas et al, 2000;Hartness et al, 2001). Therefore, the possible functional effects of Jagged1 were analyzed by measuring NA release in basal condition and after K + -evoked depolarization.…”
Section: Loss and Recovery Of Varicosities Are Accompanied By Functiomentioning
confidence: 99%
“…These reactions including MARCKS phosphorylation, disassembly of cortical F-actin structure, and the potentiation of Ca 2+ -evoked secretion are reported to be inhibited by a synthetic peptide of the PSD of MARCKS. In SH-SY5Y cells, overexpression of MARCKS leads to a decrease in the K + -evoked noradrenaline release (8). Although it is well-known that MARCKS phosphorylation responds to several kinds of stimuli, it is not plausible that all these stimuli activate PKC to phosphorylate PSD.…”
Section: Marcks Is a Candidate For A Regulatory Component Of Neurotramentioning
confidence: 99%
“…On the other hand, it is demonstrated that PKC-dependent phosphorylation of myristoylated alanine-rich C kinase substrate (MARCKS) occurs coincidently with F-actin disassembly and potentiation of catecholamine release in a permeabilized chromaffin cells (7). Overexpression of MARCKS is reported to decrease catecholamine release from K + -stimulated human neuroblastoma (8). These results seem to be attributed to MARCKS-dependent reorganization of F-actin structure, which may allow the vesicles to access the presynaptic membrane and its adjacent area, the so-called "active zone".…”
Section: Introductionmentioning
confidence: 99%